Technical features of Norwood procedure as the most important factor, affecting the outcome of treatment of single-ventricle patients with obstructed systemic output - A. A. Avramenko; S. M. Khokhlunov (Вестник хирургии имени И.И. Грекова, 2019)
The objective was to improveNorwood procedure outcomes by discovering optimal surgical technique and perfusion strategy.Material and methods. Results of treatment of single-ventricle patients with obstructed systemic output during 2005–2017 were analyzed (64 patients). 61 patients underwentNorwood procedure. Outcomes were compared between groups with different perfusion strategies and different methods of aortic arch reconstruction.Results. Mortality in two-regional perfusion group was 23 %, in group of circulatory arrest and selective cerebral perfusion – 53 % (p=0.020). Early aortic obstruction was a risk factor of mortality (p=0.024). Median time of freedom from obstruction of aorta was 3 days in xenopericardium group, 76 days in pulmonary allograft group, and 390 days in isthmus resection and pulmonary allograft group (p=0.002).Conclusion. Two-regional perfusion and aortic arch repair with pulmonary allograft patch after isthmus resection are our methods of choice as they allow to reduce the incidence of complications afterNorwood procedure.